School ethos and adolescent gambling: a multilevel study of upper secondary schools in Stockholm, Sweden - Sara Brolin Låftman; Bitte Modin; Gabriella Olsson; Kristina Sundqvist; Johan Svensson; Peter Wennberg (BMC, 2020)
Abstract Background Gambling is not uncommon among adolescents, and a non-trivial minority has serious problems with gambling. Therefore, enhanced knowledge about factors that may prevent against problematic gambling among youth is needed. Prior research has shown that a strong school ethos, which can be defined as a set of attitudes and values pervading at a school, is associated with a lower inclination among students to engage in various risk behaviours. Knowledge about the link between school ethos and adolescent gambling is however scarce. The aim of the study was to investigate the association between teacher-rated school ethos and student-reported gambling and risk gambling, when controlling also for sociodemographic characteristics at the student- and the school-level. Methods Data from two separate cross-sectional surveys were combined. The Stockholm School Survey (SSS) was performed among 5123 students (aged 17-18 years) in 46 upper secondary schools, and the Stockholm Teacher Survey (STS) was carried out among 1061 teachers in the same schools. School ethos was measured by an index based on teachers' ratings of 12 items in the STS. Adolescent gambling and risk gambling were based on a set of single items in the SSS. Sociodemographic characteristics at the student-level were measured by student-reported information from the SSS. Information on sociodemographic characteristics at the school-level was retrieved from administrative registers. The statistical method was multilevel regression analysis. Two-level binary logistic regression models were performed. Results The analyses showed that higher teacher ratings of the school's ethos were associated with a lower likelihood of gambling and risk gambling among students, when adjusting also for student- and school-level sociodemographic characteristics. Conclusions This study showed that school ethos was inversely associated with students' inclination to engage in gambling and in risk gambling. In more general terms, the study provides evidence that schools' values and norms as reflected by the teachers' ratings of their school's ethos have the potential to counteract unwanted behaviours among the students.